Transformation of local wisdom values to build elementary and secondary school students’ characters: a case study in Serang Regency, Banten Province, Indonesia - Muhammad Turhan Yani; Tamsil; Raden Roro Nanik Setyowati; Budi Jatmiko; Ahmad Ajib Ridlwan (Cogent Education)
Local wisdom is an important source of community value for developing student character. This study aims to describe the character-building process for elementary and secondary school students through the transformation of Sundanese local wisdom in Serang Regency, Banten Province, Indonesia. This study aims to analyze local wisdom as a source of noble value in building student character and how character-building occurs. This research is classified as a case study with a qualitative approach. Data was obtained from interviews, observations, and documentation. Interviews were conducted with 100 students, 4 (four) school principals, and 4 (four) teachers. The interview results were then discussed with community and religious leaders and teachers in a group discussion forum. The results showed that local wisdom became an important source of value in forming students’ character at school in the form of wise sentences (proverbs), traditions, and other cultural symbols. The noble values transformation in building students’ character was done in four ways: education and habituation, competitions on science and technology, social programs, pamphlets, and banners. The transformation of noble values conceived from the Serang community’s local wisdom effectively built students’ good character, covering honesty, intelligence, caring, and resilience.